Evaluation the effect of microorganisms on germination, growth and physiological indices of pumpkin (Cucurbita pepo var.styriaca) under salinity stres - esmaeil mousavi; Heshmat Omidi (علوم و فناوری بذر ایران, 2021)
To study the effect of bio-priming on germination, growth and physiological indices of pumpkin under salinity a factorial experiment in a completely randomized design was conducted in three replications. Experimental treatments were salinity at four levels (zero, 40, 80 and 120 mM) and biological pre-treated at eight levels (control, inoculation with Trichoderma harzianum fungi, Azoto bio-fertilizer, phosphate bio-fertilizer, both bio-fertilizer, combination of fungi and azoto bio-fertilizer, combination of fungi and phosphate bio-fertilizer, fungi and both bio-fertilizer). Phosphate biofertilizer threatment had maximum positive effect on percent germination with increasing the salinity. In combination of fungi and phosphate biofertilizer with increasing the salinity levels reduced fewer the germination coefficient. Low levels of salinity had positive effect on growth indices and caused increase that this indices. Maximum seedling length in different levels of salinity obtained in combination of both biofertilizers treatment. Maximum amount of vigor weighted index obtained in fungi treatment and increasing of salinity level caused that reduced this trait. With increasing of salinity level reduced dry weight of seedling and was maximum amount in fungi treatment. The use of microorganisms caused that reduced the negative effect of salinity. With salinity increasing increased the amount of antioxidant enzymes and the use of biopriming treatments more increased the amount of these enzymes in compared to control which show these treatments was effective in reduction of salinity effect by means of increasing the enzymes. Using of microorganisms with more increasing antioxidant enzymes in compared to control caused reduction of negative effect of salinity stress.